Can agricultural digitalization improve agricultural export quality? - Zhichao Jiang; Xiaorun Wang; Pengling Liu (PLoS ONE, 2026)
In the context of an evolving international trade landscape, agricultural digitalization represents a critical pathway for enhancing agricultural export quality (AEQ) and accelerating the development of a modern agricultural powerhouse. Using panel data from 34 provincial administrative regions in China from 2001 to 2024, this study constructs a comprehensive evaluation index system for agricultural digitalization and conducts a multidimensional analysis employing an individual, time two-way fixed effects model, a mediation effects model, and a moderation effects model. The results indicate that: (1) agricultural digitalization significantly promotes improvements in AEQ, and this conclusion remains robust after addressing endogeneity concerns and conducting a series of robustness tests; (2) accelerating agricultural technological progress, improving the level of agricultural human capital, and enhancing agricultural logistics efficiency constitute important transmission pathways through which agricultural digitalization affects AEQ; (3) the effect of agricultural digitalization on AEQ exhibits multidimensional heterogeneity, with stronger marginal effects observed in eastern regions, major grain-producing areas, and regions with higher levels of marketization; and (4) policy support and market openness play significant moderating roles in the relationship between agricultural digitalization and AEQ. Based on these findings, this study proposes several policy recommendations, including accelerating the development of agricultural digitalization, promoting agricultural technological progress, and establishing a scientific and regionally tailored agricultural digital system that reflects local conditions. These recommendations provide a scientific basis for policymaking aimed at leveraging agricultural digitalization to enhance AEQ.